99mTc-Radiolabeled Silica Nanocarriers for Targeted Detection and Treatment of HER2-Positive Breast Cancer - Rainone P (Dove Medical Press, 2021)
Paolo Rainone,1– 3 Antonella De Palma,4 Francesco Sudati,5 Valentina Roffia,4 Valentina Rigamonti,6 Lucia Salvioni,6 Miriam Colombo,6 Marilena Ripamonti,2 Antonello Enrico Spinelli,7 Davide Mazza,7 Pierluigi Mauri,4 Rosa Maria Moresco,1,2,7 Davide Prosperi,6 Sara Belloli2,7 1Department of Medicine and Surgery, University of Milano-Bicocca, Monza, 20900, Italy; 2Institute of Molecular Bioimaging and Physiology of CNR, Segrate, 20090, Italy; 3Doctorate School of Molecular and Translational Medicine, University of Milan, Milan, Italy; 4Institute of Biomedical Technologies of CNR, Segrate, 20090, Italy; 5PET and Nuclear Medicine Unit, San Raffaele Scientific Institute, Milan, 20132, Italy; 6NanoBioLab, Department of Biotechnology and Biosciences, University of Milano-Bicocca, Milan, 20126, Italy; 7Experimental Imaging Center, San Raffaele Scientific Institute, Milan, 20132, ItalyCorrespondence: Sara BelloliInstitute of Molecular Bioimaging and Physiology of CNR, Via Fratelli Cervi 93, Segrate, 20090, ItalyTel +39 02 26433640Fax +39 02 26432717Email belloli.sara@hsr.itIntroduction: The overexpression of Human Epidermal Growth Factor Receptor 2 (HER2) is usually associated with aggressive and infiltrating breast cancer (BC) phenotype, and metastases. Functionalized silica-based nanocarriers (SiNPs) can be labeled for in vivo imaging applications and loaded with chemotherapy drugs, making possible the simultaneous noninvasive diagnosis and treatment (theranostic) for HER2-positive BC.Methods: Firstly, FITC-filled SiNPs, were engineered with two different amounts of Hc-TZ (trastuzumab half-chain) per single nanoparticle (1:2 and 1:8, SiNPs to Hc-TZ ratio), which was 99mTc-radiolabeled at histidine residues for ex vivo and in vivo biodistribution evaluations. Secondly, nanoparticles were loaded with DOX and their in vitro and ex vivo/in vivo delivery was assessed, in comparison with liposomal Doxorubicin (Caelyx). Finally, the treatment efficacy of DOX-SiNPs-TZ (1:8 Hc-TZ) was evaluated in vivo by PET and supported by MS-based proteomics profiling of tumors.Results: SiNPs-TZ (1:8 Hc-TZ) tumor uptake was significantly greater than that of SiNPs-TZ (1:2 Hc-TZ) at 6 hours post-injection (p.i.) in ex vivo biodistribution experiment. At 24 h p.i., radioactivity values remained steady. Fluorescence microscopy, confirmed the presence of radiolabeled SiNPs-TZ (1:8 Hc-TZ) within tumor even at later times. SiNPs-TZ (1:8 Hc-TZ) nanoparticles loaded with Doxorubicin (DOX-SiNPs-TZ) showed a similar DOX delivery capability than Caelyx (at 6 h p.i.), in in vitro and ex vivo assays. Nevertheless, at the end of treatment, tumor volume was significantly reduced by DOX-SiNPs-TZ (1:8 Hc-TZ), compared to Caelyx and DOX-SiNPs treatment. Proteomics study identified 88 high stringent differentially expressed proteins comparing the three treatment groups with controls.Conclusion: These findings demonstrated a promising detection specificity and treatment efficacy for our system (SiNPs-TZ, 1:8 Hc-TZ), encouraging its potential use as a new theranostic agent for HER2-positive BC lesions. In addition, proteomic profile confirmed that a set of proteins, related to tumor aggressiveness, were positively affected by targeted nanoparticles.Keywords: HER2-positive BC, targeted silica nanoparticles, TZ-half chain conjugation, 99mTc-radiolabeling, SPECT imaging, doxorubicin-loaded nanoparticles